Recovery and separation of cellulose from sawdust wood hydrolysates using membrane creator: effect of transmembrane pressure (TMP) and cross flow velocity (CFV) - Mohamad Afis, Adnan (2010)
Cellulose is among the most important natural resources that contain polysaccharides. In this study, the effect of transmembrane pressure (TMP) and cross-flow velocity (CFV) on permeate flux during the recovery and separation of cellulose from sawdust wood hydrolysates by using membrane reactor was investigated. Two-stage pretreatment was performed by using dilute sodium hydroxide (NaOH) and followed by dilute sulfuric acid (H2SO4) for about 24 hours at 75ºC respectively. Separation of cellulose from sawdust wood hydrolyzed was performed by using ceramic microfiltration membrane with pore size of 0.9μm and effective surface area of approximately 0.03m2 for 60 minutes at 50ºC respectively. The experiment was conducted at five different values of TMP and CFV range from 0.5 to 2.5 bars and 0.02 to 0.18 m/s. During the filtration experiments, the permeate flux through microfiltration membrane was relatively high. At first, the highest flux was found at an optimum TMP and CFV of 1.5 bars and 0.14 m/s with percentage of flux decline at 2.68% and 11.75% respectively. After optimization using Response Surface Methodology (RSM), the maximum permeate flux obtained was at 247.614 L/m2.h at an optimum TMP of 1.0 bar and optimum CFV of 0.14 m/s within the duration of 20 minutes of filtration. As conclusion, TMP and CFV give significant effect on permeate flux.